Omnichannel strategy and the distribution of public services in Spain - Manuel Rey-Moreno; Cayetano Medina-Molina (Journal of Innovation & Knowledge (JIK), 2016)
There are numerous benefits linked to application of e-Government, both for public organizations (greater efficiency, costs savings, etc.) and for citizens (accessibility, availability, etc.). These have brought about a generalized commitment of most governments to its implementation.Although the population usually tends to be very satisfied with these new technological products, their adoption rates have stabilized. At the same time, the levels of use of traditional interaction channels have remained the same or, depending on the aim, have even increased. The main reason for this is, perhaps, to be found in citizens seeing these new channels as a supplement to traditional channels and not as an alternative, which can substitute them.In order to achieve a generalized acceptation and use of e-Government, it is necessary to start out from knowing the citizens' needs. The marketing field has proposed different strategies to respond to this challenge. These range from multichannel management to multichannel marketing and an omnichannel experience. This work presents the current situation of the development of e-Government in Spain, showing the real applicability and degree of efficacy of the previously mentioned strategies to increase the citizens' rate of use of e-Government, compared to traditional management channels.
Keywords: M38; M15; H89; 650; e-Government; Multiplicity of channels; Omnichannel strategy; Citizens' preferences